تطوير الوسيلة التعليمية فلاش ماكروميديا لتعليم المفردات العربية علي أساس الوسائل المتعددة التفاعلية في تحسين نتائج طلاب بالمدرسة - Endang Oktavia Arida; Mohamed Farid Gaballah; Niwari Niwari (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2023)
Learning media in learning activities is so important. For both teachers and students, learning media plays a important role in the teaching and learning process. Learning media is to attract students' interest as well as a tool to make it easier for students to understand Arabic lessons. Teachers will find it difficult to increase the effectiveness of learning without media. Likewise with students, without media they will face obstacles in learning. Especially when the teacher explains the lesson quickly and unclearly, causing students not to understand it. The results obtained by the researcher from two previous questions are the steps for developing Macro Flash learning media in interactive multimedia-based Arabic learning to improve student learning outcomes and the effectiveness of the learning media that has been developed. The results type is a research and development. With the Borg and Gall development method.